2014
DOI: 10.5897/ajcpath14.012
|View full text |Cite
|
Sign up to set email alerts
|

Testicular Alteration in Over Dosage of Azathioprine: A Histological and Histochemical Study in Wistar Rats

Abstract: Aim:The use of Azathioprine (AZA) in the prevention of organ rejection during transplantation has been documented for different organs of the body. In this study, we investigated the effects of azathioprine on the integrity of the testis of Wistar rats using histological and histochemical techniques. Methods: Eighteen adult male Wistar rats with mean weight 210±2.65 g were randomly assigned into three groups. Group I (control) received 1 ml of normal saline "per os" (p.o), group II animals received 10 mg/kg AZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 8 publications
2
6
0
Order By: Relevance
“…This agrees with the results of Sachin et al [35] and Onanuga et al [36] who noticed a decrease in body and testicular weight of mice treated with AZP and was rationalized by the decrease of the anabolic effect of testosterone. The study of Bairyk et al [37], reported that oxidative stress reduced enzymatic and nonenzymatic level in Leydig cells and caused reduction of testosterone.…”
Section: Discussionsupporting
confidence: 92%
“…This agrees with the results of Sachin et al [35] and Onanuga et al [36] who noticed a decrease in body and testicular weight of mice treated with AZP and was rationalized by the decrease of the anabolic effect of testosterone. The study of Bairyk et al [37], reported that oxidative stress reduced enzymatic and nonenzymatic level in Leydig cells and caused reduction of testosterone.…”
Section: Discussionsupporting
confidence: 92%
“…Oral AZA administration in male rats caused a significant decrease in body and testicular weight and reduced serum testosterone, LH, and FSH levels, which we believe may be attributed to the oxidative stress [ 51 ] induced by this drug or decrease in the anabolic effects of testosterone [ 52 , 53 ]. This hypothesis is consistent with the data reported by Duan et al (2017) [ 54 ], who found a marked decline in serum FSH and LH levels and increased.…”
Section: Discussionmentioning
confidence: 99%
“…AZA inhibits DNA synthesis in cells that proliferate rapidly, such as T and B lymphocytes [38]. AZA harms fertility, causing damage to the testicular structure and disrupting testicular integrity in mice, as has been previously reported [25]. AZA has been demonstrated to reduce immunity and lowers number of killer cells, according to Honkila et al [39].…”
Section: Discussionmentioning
confidence: 87%
“…Only 40 mg of each tablet, which was powdered, was used. The 40 mg powder was then diluted in 10 mL normal saline solution (Sodium chloride 0.9% solution) and used at a therapeutic dosage of 20 mg/kg body weight every day for 2 weeks, according to Onanuga et al [25]. The treatment was administrated orally through a stomach tube.…”
Section: Introductionmentioning
confidence: 99%